Figurative Language in Tame Impala’s Song Lyrics - Oktavia, dhea (Jurnal Bahasa Inggris Terapan, 2023)
This study is aimed to identify phrases and clauses containing figurative language in Tame Impala’s song lyrics. The theory of figurative language used in this study is the one proposed by Mezo (metaphor, simile, personification, metonymy, synecdoche, hyperbole, and litotes). A qualitative method through a document analysis strategy was applied to this research. The object of this analysis is based on the lyrics of Tame Impala's songs on the four albums, including Innerspeaker (2010), Lonerism (2012), Currents (2015), and The Slow Rush (2020). The result shows that the most common figurative language found in Tame Impala’s song lyrics is Metaphor (38%), Simile (21%), and Personification (19%). It indicates that most of the song lyrics of Tame Impala visualize comparisons and deepen understanding so that it makes readers increase their critical thinking as well as see old things in new ways.